2010
DOI: 10.1007/s00432-010-0951-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of systemic inflammatory response in renal cell carcinoma: a systematic review and meta-analysis

Abstract: The systemic inflammatory response predicted poor survival in patients with renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 49 publications
5
62
0
2
Order By: Relevance
“…Numerous studies have shown that CRP is a significant prognostic factor for RCC patients treated with surgery and/or systemic therapy. Our also evidence demonstrates CRP is associated with poor prognosis of RCC which is consistent with a previous meta-analysis study (Wu et al, 2011). The prognostic significance of CRP has been shown with its power for in urological cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have shown that CRP is a significant prognostic factor for RCC patients treated with surgery and/or systemic therapy. Our also evidence demonstrates CRP is associated with poor prognosis of RCC which is consistent with a previous meta-analysis study (Wu et al, 2011). The prognostic significance of CRP has been shown with its power for in urological cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the plasma concentration of C-reactive protein in RCC-bearing patients (Hu et al, 2014;Ito et al, 2006;Jagdev et al, 2010;Karakiewicz et al, 2007;Lamb, McMillan, Ramsey, & Aitchison, 2006;Steffens et al, 2012) and the presence of an inflammatory gene signature in RCC (Romero et al, 2006;Tan et al, 2011) are linked to a higher tumor grade and positive metastatic status at diagnosis and poor prognosis. In addition, other inflammatory markers are related to poor survival in RCCbearing patients, including an augmented erythrocyte sedimentation rate, leukocytosis, thrombocytosis, and the increased plasmatic concentrations of IL-6 and TNF-α (Dosquet, Coudert, Lepage, Cabane, & Richard, 1997;Dosquet et al, 1994;Escudier et al, 2014;Fox et al, 2013;Negrier et al, 2004;Pichler et al, 2013;Wu et al, 2011;Yoshida et al, 2002). In vitro studies reinforce this concept, since several proinflammatory cytokines (eg, IL-6, TNF-α, hypoxia-inducible factor-α, and matrix metalloproteinase-2) are preferentially produced by the RCC cell lines exhibiting the highest malignant potential (Chuang et al, 2008;Ho et al, 2012;K€ onig et al, 1999).…”
Section: The Ccrcc Tumor Microenvironmentmentioning
confidence: 98%
“…An elevated PLT level was associated with poor OS (HR 2.24, 95% CI 1.87–2.67, p < 0.001) and CSS (HR 2.59, 95% CI 1.92–3.48, p < 0.001) in the analysis of all stages together. In localized disease, elevated PLT count was associated with poor CSS (HR 5.09, 95% CI 2.41–10.73, p < 0.001) and RFS (HR 6.68, 95% CI 3.35–13.34, p < 0.001) [33, 34]. Additionally, an elevated PLT level was significantly associated with TNM stage (OR 3.11, 95% CI 1.59–6.06, p = 0.001), pathological T stage (OR 3.13, 95% CI 2.60–3.77, p < 0.001), lymph node metastasis (OR 4.01, 95% CI 2.99–5.37, p < 0.001), distant metastasis (OR 3.85, 95% CI 2.46–6.04, p < 0.001), Fuhrman grade (OR 3.70, 95% CI 3.00–4.56, p < 0.001), tumor size (OR 4.69, 95% CI 2.78–7.91, p < 0.001), and Eastern Cooperative Oncology Group score (OR 5.50, 95% CI 3.26–9.28, p < 0.001) [34].…”
Section: Discussionmentioning
confidence: 99%